Treatment-resistant or difficult-to-treat depression: a consensus on the pharmacotherapy challenges and considerations for the health care system in Greece - Kyriakos Souliotis; Kyriakos Souliotis; Christina Golna; Myrto Samara; Eva-Maria Tsapakis; Vasilios P. Bozikas; Thomas N. Hyphantis; Nikolaos Smyrnis; Nikos Stefanis (Frontiers in Psychiatry)
IntroductionGlobally, there is limited scientific consensus on the definition of Treatment Resistant Depression (TRD) or Difficult to Treat Depression (DTD) and even greater challenges are being reported with its management. In Greece, the last available guidelines on depression from 2015 make no reference to TRD/DTD management. This study aims to inform the definition of TRD or DTD and propose a pathway for its integrated management in the context of the Greek National Health System (NHS).MethodsIndividual interviews with clinical experts based on a structured interview guide were conducted in November 2022 to explore consensus on the definition, key challenges, and prospects for the management of TRD/DTD in Greece. Results were combined in a manuscript that was circulated amongst authors for comments and sign off.ResultsParticipants preferred the use of the DTD term over TRD, though noted that using the term TRD may be more amendable to wider scientific audiences. They also agreed on the need to set bold treatment goals and assess optimal treatment dose, duration, and adherence, in the context of shared decision making, prior to confirming a diagnosis as TRD/DTD and proposing a treatment strategy. Integration of patient management with use of mobile mental health units, Mental Health Centers and tertiary Centers of Excellence would promote patient centricity, accessibility, affordability as well as help develop an evidence basis for the further customization and evolution of mental health policies in the future.ConclusionThis is the first study to discuss and define the challenge of TRD/DTD in Greece and propose a structured pathway for its integrated management in the context of the Greek NHS, allowing for the country’s geographic disparities, history of burden of mental health and socioeconomic specificities, including stigma surrounding a mental health diagnosis.